Medical students' learning orientation regarding interracial interactions affects preparedness to care for minority patients: a report from Medical Student CHANGES. Issue 1 (December 2016) - Burgess, Diana; Burke, Sara; Cunningham, Brooke; Dovidio, John; Hardeman, Rachel; Hou, Yuefeng; Nelson, David; Perry, Sylvia; Phelan, Sean; Yeazel, Mark; van Ryn, Michelle
Abstract Background There is a paucity of evidence on how to train medical students to provide equitable, high quality care to racial and ethnic minority patients. We test the hypothesis that medical schools' ability to foster a learning orientation toward interracial interactions (i.e., that students can improve their ability to successfully interact with people of another race and learn from their mistakes), will contribute to white medical students' readiness to care for racial minority patients. We then test the hypothesis that white medical students who perceive their medical school environment as supporting a learning orientation will benefit more from disparities training. Methods Prospective observational study involving web-based questionnaires administered during first (2010) and last (2014) semesters of medical school to 2394 white medical students from a stratified, random sample of 49 U.S. medical schools. Analysis used data from students' last semester to build mixed effects hierarchical models in order to assess the effects of medical school interracial learning orientation, calculated at both the school and individual (student) level, on key dependent measures. Results School differences in learning orientation explained part of the school difference in readiness to care for minority patients. However, individual differences in learning orientation accounted for individual differences in readiness, even after controlling for school-level learning orientation. Individual differences in learning orientation significantly moderated the effect of disparities training on white students' readiness to care for minority patients. Specifically, white medical students who perceived a high level of learning orientation in their medical schools regarding interracial interactions benefited more from training to address disparities. Conclusions Coursework aimed at reducing healthcare disparities and improving the care of racial minority patients was only effective when white medical students perceived their school as having a learning orientation toward interracial interactions. Results suggest that medical school faculty should present interracial encounters as opportunities to practice skills shown to reduce bias, and faculty and students should be encouraged to learn from one another about mistakes in interracial encounters. Future research should explore aspects of the medical school environment that contribute to an interracial learning orientation.